Turismo rural e agroindústria: uma alternativa para o desenvolvimento sustentável no município de Ubiratã/PR - Klein , Luciana Cristina (2021)
In recent times, farmers have been facing numerous difficulties, especially in generating income in the countryside. With this reality, non-agricultural activities arise as an increase and diversification of income, in addition to those characterized as agricultural activities, providing this part of the population with dignified living conditions. Therefore, this work aims to analyze agritourism as an economic alternative for the rural area of the municipality of Ubiratã/PR. Therefore, 12 properties that practice some type of tourist activity in rural areas, associated with family farming in this city, were researched, along with a bibliographical research reviewing and conceptualizing the theme, which evidence for the fact that it associates tourism in the rural space to agritourism, is an alternative viable income supplement for family farmers who work in agribusiness activities. The methodology used in the research was characterized by exploratory-descriptive studies, linked to the mother project, called Regional Rural Tourism Development in West Paraná, involving the municipalities of Cascavel, Ubiratã and Guaraniaçu, coordinated by the State University of West Paraná (Unioeste ), within the Regional Training Program for Local Economic Development, which for this study only used data from the city of Ubiratã. It is a qualitative approach, being also a case study. As a result of this investigation, it was possible to observe that the insertion of agritourism in activities related to the countryside and family farming is viable and feasible as a complement to the income of the families involved. As a product of the final result of this research, a map was created containing a tourist route with the properties of the family agribusiness in the municipality, containing, in addition to their location, information to aid the visitor regarding the activities practiced in each property, contributing to the attractiveness for region. Also, according to the data collected, it was possible to identify some strengths in the studied region, such as the low cost for the development of the proposal and the implementation of services on rural properties, the development of the activity in an organized manner, through associations and the constitution circuits (within the municipality and between municipalities), as well as the facility to be applied in other realities that present potential for the development of agritourism. Also, there were some limiting weaknesses for the tourist activity related to the commitment of the local government, since the development of the activity collides with actions that are its responsibility, such as the issue of local infrastructure (accesses, roads) and availability training and mentoring.